(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The role of prophylactic antibiotics in open mesh repair of inguinal hernia is still controversial. The dogmatic hernia specialists are always in favour of no use of antibiotic in case of inguinal hernia repair on contrary, many others favour the use of prophylactic antibiotic. Objective: To determine the role of prophylactic antibiotic in case of open mesh inguinal hernia surgery by a prospective randomized study. Materials and Methods: This prospective randomized interventional and observational study was conducted from March to December 2017 at Combined Military Hospital, Chattogram. Total 40 patients selected for open inguinal hernia surgery were grouped as Group-A and Group-B containing 20 in each group on the basis of systematic random sampling. The Group-A and Group-B patients were treated with a single dose of prophylactic antibiotic (1.5gm Cefuroxime) and a similar quantity of normal saline respectively. Data were recorded, compiled, edited and analyzed by SPSS version 23. Results: The mean age of Group-A and B respondents were 53.16±7.76 and 52.39±5.69 years respectively. Mean duration of surgery was 59.76±2.1 and 54.56±18.3 minutes in Group-A and B respectively. Surgical site infection (SSI) was present in 2(10%) cases of Group-A and 5(25%) of Group-B. Though it was little higher in Group-B, the difference was not statistically significant (p>0.05). Staphylococcus was most prevalent in Group-A and multiple organisms in Group-B. Conclusion: Prophylactic antibiotic is not able to significantly decrease the rate of SSI. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 18-21